Changing trend of superficial mycoses with increasing nondermatophyte mold infection: A clinicomycological study at a tertiary referral center in Assam - Debeeka Hazarika; Nazneen Jahan; Ajanta Sharma (Wolters Kluwer Medknow Publications, 2019)
Background: Superficial mycosis is the commonest infections affecting human globally. Though they do not cause mortality, their clinical significance lies in their morbidity, recurrence, and cosmetic disfigurement, thus creating a major public health problem. The infections are more prevalent in the tropical regions. The etiological agents are also seen to vary with time and geographical location. Aim: This study was carried out to find out the trend of superficial mycosis in Assam, along with a clinicomycological correlation. Materials and Methods: A total of 130 clinically diagnosed cases of superficial mycoses attending the outpatient department (OPD) of a tertiary hospital in Assam for a period of 1 year were taken up for the study. After taking the informed consent and a proper history, the clinical materials like skin scrapings, nail clippings, and infected hair were sent for mycological examination. Results: The infection was found to be more prevalent among males than females (M:F, 3:2) and among the farmers and laborers (24.61%). Tinea corporis was the commonest clinical type (21.5%). Among the fungal isolates, dermatophytes were the most frequent isolates (43.54%), out of which Trichophyton rubrum was commonest. nondermatophyte moulds like Fusarium, Aspergillus, Scopulariopsis, Trichosporon, and Penicillium spp. were isolated. Conclusion: The epidemiology of fungal infection and the causative fungi is seen to vary geographically and with time. This study reflects the changing trend of fungal infection in the north eastern region with a high rate of isolation of nondermatophyte moulds as the causative agent.